2022
DOI: 10.3390/nu14245203
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a ‘Remotely-Delivered’ Sports Nutrition Education Program on Dietary Intake and Nutrition Knowledge of Junior Elite Triathletes

Abstract: Triathlon is a physically demanding sport, requiring athletes to make informed decisions regarding their daily food and fluid intake to align with daily training. With an increase in uptake for online learning, remotely delivered education programs offer an opportunity to improve nutritional knowledge and subsequent dietary intake in athletes. This single-arm observational study aimed to evaluate the effectiveness of a remotely delivered nutrition education program on sports nutrition knowledge and the dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Our study employed a nutrition education intervention consisting of six physical sessions totaling 360 min, a strategy proven effective in similar studies with contact time ranging from 90 min ( 38 ) to 390–490 min ( 39 ) and the total number of sessions ranging from one ( 40 ) to ten ( 39 ). This approach resulted in a 7.2% improvement in SNK, which is consistent (8.3%) with a similar study conducted with adolescent swimmers ( 41 ). Previous studies investigating the effectiveness of nutrition education approaches have reported similar improvements in athlete nutrition scores, ranging from 6.4–25.2% ( 42 44 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our study employed a nutrition education intervention consisting of six physical sessions totaling 360 min, a strategy proven effective in similar studies with contact time ranging from 90 min ( 38 ) to 390–490 min ( 39 ) and the total number of sessions ranging from one ( 40 ) to ten ( 39 ). This approach resulted in a 7.2% improvement in SNK, which is consistent (8.3%) with a similar study conducted with adolescent swimmers ( 41 ). Previous studies investigating the effectiveness of nutrition education approaches have reported similar improvements in athlete nutrition scores, ranging from 6.4–25.2% ( 42 44 ).…”
Section: Discussionsupporting
confidence: 90%